2019
DOI: 10.1103/physrevb.99.205413
|View full text |Cite
|
Sign up to set email alerts
|

Interface sharpening in miscible and isotopic multilayers: Role of short-circuit diffusion

Abstract: Atomic diffusion at nanometer length scale may differ significantly from bulk diffusion, and may sometimes even exhibit counterintuitive behavior. In the present work, taking Cu/Ni as a model system, a general phenomenon is reported which results in sharpening of interfaces upon thermal annealing, even in miscible systems. Anomalous x-ray reflectivity from a Cu/Ni multilayer has been used to study the evolution of interfaces with thermal annealing. Annealing at 423 K results in sharpening of interfaces by abou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 44 publications
3
5
0
Order By: Relevance
“…As we increase the T s , ∆ Fe increases albeit a small drop in pure Fe deposited at T s = 523 K. Such a drop in ∆ Fe can be due to an interface sharpening effect which happens due to release of defects and voids. Such interface sharpening was also evidenced recently in Fe thin films grown at 573 K [62] and also observed in earlier works [63][64][65][66]. At T s = 523 K, ∆ Fe in Fe 0.8 C 0.2 sample is still significantly smaller as compared to Fe but when samples were grown at T s = 773 K, a sudden rise in ∆ Fe can be seen in Fe 0.8 C 0.2 sample.…”
Section: Depth Profiling and Fe Self-diffusion Measurementssupporting
confidence: 85%
See 1 more Smart Citation
“…As we increase the T s , ∆ Fe increases albeit a small drop in pure Fe deposited at T s = 523 K. Such a drop in ∆ Fe can be due to an interface sharpening effect which happens due to release of defects and voids. Such interface sharpening was also evidenced recently in Fe thin films grown at 573 K [62] and also observed in earlier works [63][64][65][66]. At T s = 523 K, ∆ Fe in Fe 0.8 C 0.2 sample is still significantly smaller as compared to Fe but when samples were grown at T s = 773 K, a sudden rise in ∆ Fe can be seen in Fe 0.8 C 0.2 sample.…”
Section: Depth Profiling and Fe Self-diffusion Measurementssupporting
confidence: 85%
“…In an experimental study on Fe self-diffusion in Fe/ 57 Fe multilayers, it was also found E was small (E<<1 eV) and has been explained in terms of structural defects in Fe that lead to fast Fe diffusion during initial stages which subsequently becomes smaller when defects relaxation process gets completed [74]. In a recent study also, fast Fe diffusion has been observed and explains in terms of triple junctions leading to short-circuit diffusion [62]. In a way, the fast Fe diffusion during initial stages can be understood as grain boundary (gb) diffusion.…”
Section: E Phase Transformation Mechanismmentioning
confidence: 92%
“…As we increase the T s , Fe increases albeit a small drop in pure Fe deposited at T s = 523 K. Such a drop-in Fe can be due to an interface sharpening effect that happens due to the release of defects and voids. Such interface sharpening was also evidenced recently in Fe thin films grown at 573 K [63] 013402-7 FIG. 9.…”
Section: Depth Profiling and Fe Self-diffusion Measurementssupporting
confidence: 76%
“…In an experimental study on Fe self-diffusion in Fe/ 57 Fe multilayers, it was also found E was small (E 1 eV) and has been explained in terms of structural defects in Fe that lead to fast Fe diffusion during initial stages which subsequently becomes smaller when defects relaxation process gets completed [75]. In a recent study also, fast Fe diffusion has been observed and explains in terms of triple junctions leading to short-circuit diffusion [63]. In a way, the fast Fe diffusion during initial stages can be understood as grain boundary (gb) diffusion.…”
Section: E Phase Transformation Mechanismmentioning
confidence: 92%
“…Moreover, even the presence of negligible amount of O 2 in the deposition chamber can also form oxide layer in the substratefilm interface which was also evidenced in our samples. The O 2 base pressure was ≈ 7.5×10 −10 Torr in our chamber (measured using a residual gas analyzer) [43], and it seems that this negligible amount of O 2 readily reacts with Ti forming a thin (< 2 nm) Ti 2 O 3 phase during the early stage of growth (∆H 0 f = -1521 kJ mol −1 for Ti 2 O 3 compared to -337 kJ mol −1 for TiN). Detailed fitted parameters are listed in Table 3.…”
Section: X-ray Reflectivitymentioning
confidence: 74%